Validation of ANSYS Model of Experimental Test Rig Simulating the Flow Inversion in RRs - , Sayed Elnaggar (Archives of Current Research International, 2022)
The experimental setup was built to simulate the flow inversion in natural circulation loops in research reactors (RRs). In an effort to recognize the buildup of natural circulation in RRs, pool type upward flow after the pump coasts down due to power loss, by Abdel-Latif et al. [1], was investigated. The setup consists of two vertically stacked pipes that simulate the two branches, one of which contains a test section that is composed of electrically heated, corresponding channels that simulate the core. The second one, represents the portion of the coming back pipe that is involved in the growing of core natural circulation. Several experimental tests under various conditions as the branch’s initial temperature are performed. The channel’s coolant and surface temperatures were monitored. In this study, the thermal-hydraulic (TH) behaviour of the setup is complemented by theoretical analysis using the ANSYS Fluent 17.2 code. The ANSYS Fluent model is validated against the measured values. Typically, the setup is nodlized and a code input is being prepared. The results show that ANSYS Fluent 17.2 qualitatively predicts the thermal hydraulic behaviour and associated flow inversion phenomenon of such facilities. There is a difference between the predicted and measured values, especially for the channel’s surface temperature.